Reliability and performance analysis of a mini solar home system installed in Indonesian household - Prisma Megantoro; Hafidz Faqih Aldi Kusuma; Sinta Adisti Reina; Abdul Abror; Lilik Jamilatul Awalin; Yusrizal Afif (Institute of Advanced Engineering and Science, 2022)
During the COVID-19 pandemic since early 2020 in Indonesia, the demand for electrical energy in the housing sector has increased significantly. This is due to the government’s recommendation to reduce activities on the outside and work from home, specifically for educational and entertainment activities. Those are almost recommended to be done online. Many people complain about the increase in monthly electricity payments compared to before the pandemic. The construction of solar power plants in housing/solar home systems (SHS) will reduce the electricity consumption from the public grid. This SHS installation can be used to supply some household electricity needs, such as computers, televisions, internet facilities, lighting, et cetera. In this article, the researchers discuss the performance testing of SHS with a capacity of 300 Wp. It is installed in the house buildings accompanied by the design and measurement of solar energy potential.